The essentials for stress-free management of patients with polycystic kidney disease on peritoneal dialysis. - Fatouma Toure (RDPLF, 2023)
Summary Autosomal dominant polycystic hepatorenal disease is a common chronic kidney disease. Among the proposed replacement therapies, peritoneal dialysis (PD) concerns less than 7% of polycystic patients. The underutilization of PD is due to the fear of potential technical failure due to its potential impact on the large intraperitoneal organs. To illustrate the feasibility of the use of PD with polycystic patients despite the risk of organomegaly, we report the case of a 70-year-old patient with polycystic hepatorenal disease who has been treated with peritoneal dialysis after a long history of renal transplantation and hemodialysis. The evolution of the patient on PD was satisfactory in terms of adequacy and fluid balance. We then review the literature on the specifics of the management of polycystic patients on peritoneal dialysis. The survival of patients with polycystic disease is identical in PD and hemodialysis. There is no excess risk of technical failure or peritonitis in polycystic patients being treated with PD. However, there are slightly more symptomatic hernias in polycystic patients treated with PD, though this is without impact on technical survival. The measurement of intraperitoneal pressure (IPP) is an aid to prescribing PD, allowing the volume of dialysate to be adapted for exchanges. If kidney reduction is necessary, renal artery embolization seems to be the preferred technique. It is associated with a better likelihood of technical survival, a reduction of temporary or permanent transfers to hemodialysis and a reduction of hospitalization time. In conclusion, peritoneal dialysis is a viable option for patients with polycystic hepatorenal disease despite organomegaly. Early referral to PD could preserve patients' vascular capital. Healthcare professionals should be educated about survival, technical failure, peritonitis, symptomatic hernias, and the use of PIP to optimize the management of polycystic patients on PD.